2022
DOI: 10.1155/2022/4419955
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Factors Influencing the Fermentation Process of Teff (Eragrostis teff) and Other Cereal-Based Ethiopian Injera

Abstract: Fermented foods and beverages are the product of the enzymaticcally transformed food components which are acived by different microorganisms. Fermented foods have grown in popularity in recent years because of their alleged health benefits. Biogenic amines, bioactive peptides, antinutrient reduction, and polyphenol conversion to physiologically active chemicals are all possible health benefits of fermentation process products. In Ethiopian-fermented foods, which are mostly processed using spontaneous fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 71 publications
1
15
0
1
Order By: Relevance
“…Another interesting property of probiotic is lysozyme tolerance. Özkan et al and Mengesha et al [41,42] revealed that Lactobacillus (L.) strains isolated from traditional Turkish Tulum cheeses showed moderate lysozyme tolerance while VN2, VN3, VN5, and VN7 demonstrated strong lysozyme tolerance in 30 min and moderate tolerance in 60 min similar to Özkan et al [41]. Furthermore, Guariglia-Oropeza and Helmann [43] mentioned that the extracytoplasmic factor on (ECF) sigma (σ) factors especially σ w had involved in lysozyme resistance property.…”
Section: Discussionmentioning
confidence: 79%
“…Another interesting property of probiotic is lysozyme tolerance. Özkan et al and Mengesha et al [41,42] revealed that Lactobacillus (L.) strains isolated from traditional Turkish Tulum cheeses showed moderate lysozyme tolerance while VN2, VN3, VN5, and VN7 demonstrated strong lysozyme tolerance in 30 min and moderate tolerance in 60 min similar to Özkan et al [41]. Furthermore, Guariglia-Oropeza and Helmann [43] mentioned that the extracytoplasmic factor on (ECF) sigma (σ) factors especially σ w had involved in lysozyme resistance property.…”
Section: Discussionmentioning
confidence: 79%
“…The pH of 4.5 wine had the lowest TSS and highest alcohol content when compared to pH 3, 3.5, and 4. Fermentation pH is a very important factor in cell development as well as alcohol yield (Hossain et al, 2017;Mengesha et al, 2022). The better pH for yeast and lactic bacteria is around 4.5 although the preferred wine pH is about 3.6 (Pradip et al, 2016).…”
Section: Values Are Expressed As Mean ± Se Of Triplicate Determinatio...mentioning
confidence: 99%
“…Values around 70-80% and higher at converting hexoses can be reached, despite their inactivity with xylose-the main pentose of hemicellulose (Hasner et al, 2015). There are other types of microorganisms popular for being able to ferment hexoses and pentoses, such as Scheffersomyces stipitis and Candida shehatae; however, with limitations such as low consumption of sugars (Mengesha et al, 2022).…”
Section: Fermentationmentioning
confidence: 99%